Le Fonds d’assurance responsabilité professionnelle du Barreau du Québec - Langlois, René (Assurances, 1991)
For the past two years, the primary professional liability insurance has been replaced, for Quebec lawyers, by a fund administered by the Quebec Bar. We thank the author, Me René Langlois, who is General Manager of the Fund, to summarize the new self-insurance regime covering any claim up to $500,000 made against lawyers. Comments are offered on the implementation, the rules concerning premiums, the coverages, and the claims' administration.